Dental topography and dietary specialization in Papionini primates - Avià, Yasmina; Romero, Alejandro; Estebaranz-Sánchez, Ferran; Pérez-Pérez, Alejandro; Cuesta-Torralvo, Elisabeth; Martínez, Laura Mónica (Frontiers in Ecology and Evolution, 2022)
Our understanding of primate adaptive evolution depends on appreciating the way in which dental functional morphology affects food processing. The Papionini tribe of Cercopithecoidea primates shows great dietary versatility and ecological adaptations to resource seasonality across the African and Asian ecosystems, however, there are few studies focusing on the occlusal topography of the bilophodont teeth and the effect of tooth wear in the crown shape. Here, we explore the relationship between wear-related dental functional morphology and dietary ecological constraints within the Papionini. Three-dimensional (3D) polygonal meshes of the upper permanent molar row (M1-3) were obtained in a large papionine sample (838 specimens) of known dietary preferences including species from six genera (Cercocebus, Lophocebus, Macaca, Mandrillus, Papio, and Theropithecus). All the sample was classified in four diet categories and four topographic metrics (orientation patch count rotated, OPCR; Dirichlet normal energy, DNE; occlusal relief, OR; and ambient occlusion, portion de ciel visible, PCV) were measured for each tooth-type according to wear stage (lightly and moderately worn) to determine diet-related interspecific morphological changes with long-term functionality. The results indicate that hard-object feeders (Cercocebus and Lophocebus) and grass eaters (Theropithecus gelada) exhibit a pattern of occlusal complexity (OPCR), surface curvature (DNE), relief (OR), and morphological wear resistance (PCV) that is significantly different from the omnivores and folivore-frugivore species (Mandrillus and Macaca) despite the overall homogeneity of the bilophodont dentition. A multifactorial ANOVA showed that the topographic metrics were sensitive to tooth wear as expected. The results also indicate that the interspecific variability of dental topography of the upper molars reflects dietary specializations rather than phylogenetic proximity. These findings support the hypothesis that evolutionary convergence processes could have affected the Papionini, clustering the hard-object feeders (Lophocebus and Cercocebus) together in the morphospace, and clearly discriminating this group from the graminivorous and frugivores-folivores.